Content validation of hopelessness in Slovakia and Czech Republic - Gurková, Elena; Ziaková, Katarína; Cáp, Juraj (International journal of nursing terminologies and classifications, 2011)
PURPOSE: The purpose of this study was to validate the content of nursing diagnosis hopelessness in Slovak and Czech social and cultural contexts. METHODS: The Fehring's Diagnostic Content Validity Model was used to measure the importance of diagnostic characteristics of hopelessness. FINDINGS: Only three NANDA characteristics and five Nowotny Hope Scale characteristics have reached the value of weighted average of the scores for defining characteristics. CONCLUSION: NANDA characteristics are concerned with the affective-behavioral dimension of hopelessness. Nowotny Hope Scale characteristics that reached high importance in our study are concerned with its cognitive-temporal dimension. IMPLICATIONS FOR NURSING PRACTICE: The defining characteristics of hopelessness identified in our study could be tested in the development of instrument to measure hope in clinical practice.
Keywords: dospělí; Psychometrics; Nursing Diagnosis; psychometrie; Adult; Reproducibility of Results; Morale; Slovakia; lidé; Affective Symptoms; faktorová analýza statistická; reprodukovatelnost výsledků; psychiatrické posuzovací škály; Czech Republic; Česká republika; morálka; ošetřovatelská diagnóza; Slovenská republika; Factor Analysis, Statistical; afektivní symptomy; Psychiatric Status Rating Scales; Humans